GAMBARAN KETERATURAN MENGONTROL TEKANAN DARAH PADA PASIEN HIPERTENSI DI PUSKESMAS KEDURUS SURABAYA - Delly Amansyah Tohari; Umdatus Soleha (Jurnal Ilmiah Kesehatan, 2016)
Overview of the regularity of blood pressure control in hypertensive patients Patient with hypertension in the PHC Kedurus obtained control blood pressure every 3 months diligently, and at several other patient are rarely control. Regularity in controlling blood pressure can prevent the recurrence of hypertension. The purpose of this study to determine the regularity Overview blood pressure control in hypertensive patient at the health center Kedurus Surabaya. The study used descriptive design. The population involved 83 peoples with hypertension one stadium in the PHC Kedurus Surabaya. Researh sample 69 taken use Probability sampling techniques of sampling with simple random sampling technique. Variable research is regularity control blood pressure in hypertensive patient collect data used observation sheet. The result showed that 69 respondents almost all (85,5%) have a regular degree of regularity when their blood pressure checked. Results Chi-Square obtained, meaning the picture order to control blood pressure in hypertensive patients in PHC Kedurus Surabaya. Regular blood pressure control could prevent the recurrence of hypertension and lowers effectively. Patients are expected to take medication regularly to lower blood pressure.